A new species of Eremias (Squamata: Lacertidae) from the arid mountains of Pakistan - Masroor, Rafaqat; Khisroon, Muhammad; Khan, Muazzam Ali; Jablonski, Daniel (Zootaxa, 2020)
A new, morphologically distinctive lacertid lizard of the genus Eremias (Rhabderemias) is described from the arid mountains of northwestern Balochistan Province in Pakistan. Eremias kakari sp. nov. has an isolated distribution and can be easily distinguished from all other species of mainly desert subgenus Rhabderemias (E. andersoni, E. cholistanica, E. fasciata, E. lineolata, E. pleskei, E. scripta, E. vermiculata). Apart from other differences, E. kakari sp. nov. can be distinguished from geographically close members of the subgenus Rhabderemias (E. cholistanica, E. fasciata, and E. scripta) by having a single row of subdigital lamellae and a complete row of lateral scales and hence three scales around the penultimate phalanx of 4th toe. The new species is morphologically (dorsal pattern) very similar to E. fasciata but can be distinguished from this species for having 22–26 subdigital lamellae under 4th toe, 48–55 dorsal scales across midbody, ventrals in 11–14 oblique longitudinal series across the belly, 17–21 femoral pores and 17–21 scales in the 9th–10th annulus posterior to the postcloacal granules. The new species is currently known only from the type locality situated in the Toba Kakar Range, near to Tanishpa village. However, we expect that Eremias kakari sp. nov. would have a broader range in northwestern Pakistan and southeastern Afghanistan. An identification key for the Pakistani Eremias, together with other remarks to the new species, is presented.